Human leukocyte antigen allele linkage disequilibrium and haplotype structure in volunteer bone marrow donors of Paraná State - Costantino,Paulo Rincoski (2017)
Abstract Background Bone marrow transplantation has been used in the treatment of various diseases, especially hematologic diseases. The success of this treatment, among other factors, requires human leukocyte antigens (HLA) compatibility between patient and donor. Knowing the human leukocyte antigens allele group and haplotype frequencies as well as the linkage disequilibrium between alleles of different human leukocyte antigens loci can shorten the search time for a compatible bone marrow donor. Objective To assemble and analyze data on human leukocyte antigens frequencies available in the Laboratory of Immunogenetics and Histocompatibility (LIGH) database of the Universidade Federal do Paraná adding an estimation of the Hardy-Weinberg equilibrium and linkage disequilibrium. Methods The sample was composed of seven populations grouped by self-declared ancestry or inferred from the surname as follows: Laboratory of Immunogenetics and Histocompatibility database (all groups), descendants of Italians, Poles, and Asians, Afro-Brazilians, Mulattos (mixed ancestry) and Amerindians. Human leukocyte antigens genotyping was carried out using the polymerase chain reaction-sequence specific primers (PCR-SSP) and -sequence specific oligonucleotide (PCR-SSO) technologies. Results There were high frequencies of the HLA-A*02, HLA-B*35 and HLA-DRB1*13 allelic groups in all groups. The same was observed for the HLA-A*01-B*08-DRB1*03 haplotype except for Asian descendants. It was observed that the human leukocyte antigens Laboratory of Immunogenetics and Histocompatibility database and the Asian group are not in Hardy-Weinberg equilibrium. The Italian, Polish, Asian, Mulatto and Amerindian descendants showed haplotypes in complete linkage disequilibrium. Our results were compared with data on the human leukocyte antigens in the Paraná population available from the Brazilian Voluntary Bone Marrow Donor Registry (REDOME) and data published on the population of Curitiba and the northern region of Paraná. Conclusions Haplotypes frequent in the Asian group were not the most frequently observed in the Laboratory of Immunogenetics and Histocompatibility database and the National Bone Marrow Donor Registry for the state of Paraná. Linkage disequilibrium information may prove useful in the search for bone marrow donors for patients awaiting a suitable donor.